2016
DOI: 10.1038/ncomms10593
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutically engineered induced neural stem cells are tumour-homing and inhibit progression of glioblastoma

Abstract: Transdifferentiation (TD) is a recent advancement in somatic cell reprogramming. The direct conversion of TD eliminates the pluripotent intermediate state to create cells that are ideal for personalized cell therapy. Here we provide evidence that TD-derived induced neural stem cells (iNSCs) are an efficacious therapeutic strategy for brain cancer. We find that iNSCs genetically engineered with optical reporters and tumouricidal gene products retain the capacity to differentiate and induced apoptosis in co-cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 40 publications
0
97
0
Order By: Relevance
“…Neural stem cells (NSCs) are another commonly used tumor‐homing cells and can be therapeutically engineered with optical reporters and tumoricidal gene products without interfering with their differentiation and anticancer effects. Moreover, the engineered NSCs‐mediated delivery of the anticancer molecule TNF related apoptosis inducing ligand (TRAIL) produced 230‐fold and 20‐fold inhibitions of tumor growth in established solid and diffuse patient‐derived orthotopic brain tumor models, thereby providing an autologous cell‐based therapy . Moreover, NSCs can be used as delivery vehicles to entrap gold nanoparticles or platinum‐containing silica nanoparticles and allow deeper penetration into tumor tissues for enhanced photothermal therapy or chemotherapy …”
Section: Bioinspired Strategies From Metastasis‐associated Materials mentioning
confidence: 99%
“…Neural stem cells (NSCs) are another commonly used tumor‐homing cells and can be therapeutically engineered with optical reporters and tumoricidal gene products without interfering with their differentiation and anticancer effects. Moreover, the engineered NSCs‐mediated delivery of the anticancer molecule TNF related apoptosis inducing ligand (TRAIL) produced 230‐fold and 20‐fold inhibitions of tumor growth in established solid and diffuse patient‐derived orthotopic brain tumor models, thereby providing an autologous cell‐based therapy . Moreover, NSCs can be used as delivery vehicles to entrap gold nanoparticles or platinum‐containing silica nanoparticles and allow deeper penetration into tumor tissues for enhanced photothermal therapy or chemotherapy …”
Section: Bioinspired Strategies From Metastasis‐associated Materials mentioning
confidence: 99%
“…This suggests that iSCs can provide a readily available, safe, patient‐specific, and expandable source of stem cells. Hingtgen and co‐workers have developed induced neural stem cells (iNSCs) that were genetically engineered with a green fluorescent protein (GFP)‐luciferase fusion protein (iNSC‐GFPFL) and the proapoptotic protein, tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL; iNSC‐sTR). They found that iNSCs possessed the same unique tumor‐homing capacity as wild‐type NSCs and homed rapidly to co‐cultured glioblastoma cells in vitro and migrated to distant tumor foci in the murine brain in vivo.…”
Section: Cell‐based Biohybrid Drug Delivery Systemmentioning
confidence: 99%
“…They found that iNSCs possessed the same unique tumor‐homing capacity as wild‐type NSCs and homed rapidly to co‐cultured glioblastoma cells in vitro and migrated to distant tumor foci in the murine brain in vivo. iNSC delivery of the anticancer molecule TRAIL inhibited the growth of orthotopic human GBM xenografts and highly invasive patient‐derived xenografts, 230 and 20‐fold, respectively, as well as significantly prolonged the survival of tumor‐bearing mice . Despite these promising results, much more work is needed to elucidate the biology of these reprogrammed cells, mechanisms of the reprogramming factors, and genomic alterations that take place during the reprogramming before iSCs can be applied in a clinical setting.…”
Section: Cell‐based Biohybrid Drug Delivery Systemmentioning
confidence: 99%
“…The main crucial challenges for in vivo gene‐based GBM therapy are the blood–brain barrier and less tumor‐targeting efficiency which limit the accumulation of therapeutic concentrations in GBM. To date, many nonviral vehicles or viral vectors have been developed to enhance therapeutic gene delivery . However, only a low therapeutic efficiency can be typically achieved before the tumor‐targeting capacity of vehicles is improved.…”
Section: Introductionmentioning
confidence: 99%